Extração líquido-líquido de ácido cítrico: estudo em bancada e em colunas mecanicamente agitadas - Estêvão Magno Rodrigues Araújo (2018)
The present work aimed the study of citric acid solvent extraction in a bench scale (discontinuous tests in a single stage) and in a mechanically agitated column (Kühni) with 20 stages. The aqueous phase was a synthetic solution (pH = 1.5) with the typical citric acid concentration of industrial fermented musts (10% w/v). Exploratory experiments were carried out using different organic phases in order to select the most suitable solvent phase to further continuous extraction tests in a mechanically agitated column. The selected organic phase was: the tertiary amine Alamine® 336 (extractant), Exxal 13 tridecyl alcohol (modifier), and the aliphatic diluent Escaid 110. Next, it was studied the effects of the contact time, and of the concentrations of extractant and modifier on the citric acid extraction. Among the investigated conditions, the best ones were a contact time of 10 min, 30% w/v of Alamine® 336, 10% w/v of Exxal 13 tridecyl alcohol in Escaid110. For this condition, the equilibrium isotherm (29±2°C) was determined, and the equilibrium constant calculated (36.8 (mol.L-1 ) -1.5). It was considered that trioctylamine and citric acid complexation reaction occurs mainly with non-dissociated citric acid form, because the aqueous feed solutions pH is lower than the citric acid pKa1. It was found that 1.5 molecules of the extractant, on average, are required to react with one citric acid molecule, which can indicate that reactions with different extractant/citric acid ratios occur simultaneously. Next, the equilibrium constant and the rate constants for the direct and inverse reactions, 36,8 (mol.L-1 ) -1,5 , 2.10 (mol.L-1 ) -1.5.s-1 and 5.69x10-2 s -1 , respectively, were calculated. In the calculation of the equilibrium constant, of the extractant stoichiometric coefficient, of the citric acid concentrations in the raffinate and in the extract and of the free extractant, values of the determination coefficients (R2 ) equal or higher than 0.93 were found, representing an evidence that the results obtained through computer modeling would be very close to those obtained experimentally. Through pilot scale experiments, different volumetric flow rate ratios between the dispersed (organic) and continuous (aqueous) phases (Fd/Fc = 1/3, 2/2 and 3/1) were investigated and the citric acid concentration profiles in the aqueous and in the organic phases throughout the column were obtained. The dispersed phase hold up (), the slip velocity ( ), the mean droplet diameter of the dispersed phase (ddrop), the interfacial area between the phases (aint) and the overall mass transfer coefficient (Koc) were also determined. The best extraction condition (85%). was obtained with Fd/Fc = 2/2, and Ft = 4 L.h-1 . At this condition, it was obtained: =11,9%, =4.0 mm.s-1 , ddrop=0,50 mm, aint=690 m2 .m-3 , Koc=1.97E-6 m.s-1 , and raffinate pH=2.1